Mechanisms of cross-border economic crisis spreading and minimization of contagion risks - Сідоров, Вадим Ігоревич; Ревякін, Георгій Володимирович (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The article describes the concept of the economic crisis and the new phenomenon of economic «contagion». We analyzed international channels of economic crises spreading, their global trends and dynamics of indicators that characterize them. The paper provides concrete measures of economic «contagion» risk minimization and financial stability formation of the state.